Supramolecular Chiral Discrimination of D-Phenylalanine Amino Acid Based on a Perylene Bisimide Derivative - Bettini, Simona; Syrgiannis, Zois; Ottolini, Michela; Bonfrate, Valentina; Giancane, Gabriele; Valli, Ludovico; Prato, Maurizio (Frontiers in Bioengineering and Biotechnology, 2020)
The interaction between homochiral substituted perylene bisimide molecule and the D enantiomer of phenylalanine amino acid was monitored. Spectroscopic transitions of perylene bisimide derivative in aqueous solution in the visible range were used to evaluate the presence of D-phenylalanine. UV-visible, fluorescence, FT-IR and AFM characterizations showed that D-phenylalanine induces significant variations in the chiral perylene derivative aggregation state and the mechanism is enantioselective as a consequence of the 3D analyte structure. The interaction mechanism was further investigated in presence of interfering amino acid (D-serine and D-histidine) confirming that both chemical structure and its 3D structure play a crucial role for the amino acid discrimination. A fluorescence sensor based for D-phenylalanine was proposed. A limit of detection (LOD) of 64.2 ± 0.38 nM was calculated in the range 10-7 – 10-5 M and of 1.53 ± 0.89 µM was obtained in the range 10-5 and 10-3 M.